Integrated Channel Selector for Directing Fluid Flow Using Thermoreversible Gelation Controlled by a Digital Mirror Device. (18th March 2013) - Shirasaki, Yoshitaka; Tatsuoka, Masayasu; Yamagishi, Mai; Mizuno, Jun; Shoji, Shuichi; Funatsu, Takashi
Abstract : An integrated channel selector system employing thermoreversible gelation of a polymer was developed. Here, we show a system with3 × 3 arrayed microchannels having nine crossing points. Infrared laser irradiation was used to form gel areas at several crossing points in arranging a flow path from the inlet to one of the nine outlets passing through certain junctions and channels. The multipoint irradiation by the infrared laser was realized using a personal-computer-controlled digital mirror device. The system was demonstrated to be able to direct flow to all nine outlets. Finally, we achieved to produce flexible paths for flowing particles including side trips.